APLIKASI RANTAI MARKOV (MARKOV CHAIN) PADA PERENCANAAN SUMBERDAYA MANUSIA - Zaky, Muhammad (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2013)
This article describes how the career movements of managers and professionals within organizations may be described by a Markov chain model. Markov chain may be used to examine the movement of personnel within the organization. After briefly reviewing and illustrating Markov chain, specific applications to human resource planning are suggested. Finally, this article identifies potential limitation of Markov chain model on their appropriateness and usefulness in human resource planning